The theory of value and distribution and the problem of capital - Heinz D. Kurz (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
The paper identifies as the root of the recent controversy in the theory of capital David Ricardo's finding that competitive prices and costs of production depend not only on the methods of production employed, but also on the wage rate (or rate of profits) and change with it. A consequence of this result, whose systematic elaboration we owe to Piero Sraffa, is that systems of production cannot generally be ordered monotonically with the rate of profits. Reswitching, capital reversing, price and quantity Wicksell effects, etc., are all rooted in this fact. It is argued that the rate of profits is not determined by the marginal productivity of capital and that the equality between the two in equilibrium must not be misinterpreted as implying a causal relationship leading from the latter to the former. Attempts to assess the empirical probability of reswitching, etc., in terms of input–output tables ought to be received with many reservations for both theoretical and data-related reasons. It is further argued that problems for marginalist theory already arise in a zero-profit framework, in which compound interest effects are ruled out. Hence the seemingly unobtrusive 'laws' of input demand and output supply are a much less reliable basis to stand on than is conventionally thought. The paper concludes with some remarks on the implications of the findings in the controversy for Keynes's theory of investment.
Keywords: B12; B51; C67; D24; D46; D57; 330; capital theory; ceteris paribus clause; principle of substitution; David Ricardo; Piero Sraffa; value theory